[River and Waterfall at Thingvellir] - Streng, Evelyn Fiedler (1975)
Photograph of a river and waterfall at Thingvellir. The dark river winds through dark grey boulders forming a tall formation along the left side of the photograph. A small waterfall sits in the background, boulders breaking up the water flow. Dark rocks peek out of the river throughout. Green grass covers the side of the river and along the rocks.